Burundi : First Review Under the Three-Year Arrangement Under the Poverty Reduction and Growth Facility and Request for Waiver of Performance Criteria. (IMF Staff Country Reports; Country Report ;, 2005)
Burundi's First Review Under the Poverty Reduction and Growth Facility and Request for Waiver of Performance Criteria are discussed. Fiscal slippages emerged following the surge in petroleum prices and higher spending needs associated with the peace process and the domestically financed counterpart to much higher-than-expected project spending. Important progress has been made in pursuing peace and reconciliation and initiating the multiyear demobilization effort and security programs. Burundi has made considerable progress in normalizing relations with international creditors.